Revisiting immunity versus exposure in schistosomiasis: A mathematical modelling study of delayed concomitant immunity - Milne, Gregory C; Oettle, Rebecca C; Whittaker, Charles; Kabaterine, Narcis B; Basáñez, Maria-Gloria; Webster, Joanne P; Walker, Martin; Wilson, Shona (Oxford University Press, 2024)
Abstract The relative contributions of exposure versus acquired immunity to the epidemiology of human schistosomiasis has been long debated. While there is considerable evidence that humans acquire partial immunity to infection, age- and sex-related contact patterns with water bodies contaminated with infectious cercarial schistosome larvae also contribute to typical epidemiological profiles of infection. Here, we develop a novel schistosome transmission model that incorporates both partially protective ‘delayed concomitant’ acquired immunity—stimulated by dying worms—and host age- and sex-dependent patterns of exposure. We use a contemporary Bayesian approach to fit the model to historical individual data on exposure to infectious cercaria, eggs per gram of faeces (epg), and immunoglobulin E (IgE) antibodies specific to Schistosoma mansoni Tegumental-Allergen-Like protein 1 (SmTAL1) collected from a highly endemic community in Uganda, estimating the relative contributions of exposure and acquired immunity. We find that model variants incorporating or omitting delayed concomitant immunity describe equally well the age- and sex-specific immunoepidemiological patterns observed before intervention and 18 months after treatment. Over longer time-horizons, we find that acquired immunity creates subtle differences in immunoepidemiological profiles during routine mass drug administration that may confer resilience against elimination. We discuss our findings in the broader context of the immunoepidemiology of schistosomiasis.